2005
DOI: 10.1093/jpepsy/jsj048
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Written Emotional Disclosure in Adolescents with Asthma: A Randomized, Controlled Trial

Abstract: Written emotional disclosure improves emotional and behavioral functioning among adolescents with asthma, particularly those whose writings suggest emotional processing and cognitive restructuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 33 publications
1
65
1
3
Order By: Relevance
“…There were four studies 58,[106][107][108] evaluating unfacilitated EW on patients with asthma (Table 46). A summary of main characteristics is presented in Table 46.…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…There were four studies 58,[106][107][108] evaluating unfacilitated EW on patients with asthma (Table 46). A summary of main characteristics is presented in Table 46.…”
Section: Overviewmentioning
confidence: 99%
“…Participants were diagnosed through a clinical history of asthma and confirmed by a physician. In all studies, 58,[106][107][108] patients were reported to be on regular inhaled medication to treat persistent symptoms. Three studies [106][107][108] were conducted in the USA and Theadom et al 58 was conducted in the UK.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations